Cardioprotective properties of polyphenol concentrate in Rat model of Doxorubicin-induced Cardiomyopathy - Shulgau, Z.; Gulyayev, A.; Yermekbayeva, B.; Adilgozhina, G.; Tritek, V.; Nurgozhin, T. (My University, 2015)
Present study aimed to investigate possible cardioprotective properties of polyphenol concentrates obtained from Cabernet Sauvignon type of Kazakhstani grapes using rat model doxorubicin-induced cardiomyopathy.